Fathers’ presence and adolescents’ interpersonal relationship quality: Moderated mediation model - Li, Ao; Sun, Li; Fan, ShiQing (Frontiers in Psychology, 2023)
Introduction Most previous studies focused on the effects of fathers’ presence on adolescent development, but rarely examined the mechanisms underlying the presence of fathers on adolescent development. Moreover, previous studies ignored the impact of fathers’ way of being present on adolescent interpersonal relationships. Based on social identity theory, the present study introduced adolescents’ social responsibility as a mediating variable to explore the influence of father’s presence style on adolescents’ interpersonal. This study examined the mechanism of fathers’ way of being present on father’s presence, adolescents’ social responsibility, and their quality of interpersonal relationships; if fathers adopt a democratic approach to be present, the study examines whether teenagers are more likely to enhance their sense of social responsibility and achieve harmonious interpersonal relationships. Methods Participants were 1,942 senior high school and college students who responded to the Fatherhood Questionnaire, Social Responsibility Questionnaire, and Interpersonal Relationship Quality Diagnosis Scale. This study used PROCESS macro of SPSS 24.0 and Amos 26.0 to examine the hypotheses. Results Empirical results demonstrated that (a) fathers’ presence is directly and positively related to adolescents’ social responsibility, (b) fathers’ presence is indirectly and positively related to the quality of adolescents’ interpersonal relationships through social responsibility, and (c) parenting styles played a moderating role in the first half of the fathers’ presence on social responsibility and the quality of interpersonal relationships. Results demonstrated that more harmonious interpersonal relationships were present among teenagers when fathers adopted a democratic upbringing, and this interaction effect on interpersonal relationships was mediated by teenagers’ sense of social responsibility. Discussion The findings of this study enrich the literature by exploring the significance of emphasizing fathers’ democratic presence on teenagers’ sense of social responsibility and interpersonal relationships. The practical implications of this study are that society should encourage more fathers to be present and guide them to adopt a democratic parenting style that will benefit adolescents’ development and family well-being.